Marriage and dissolution of matrimonial ties in the Akyã custom, in Ivorian civil law and in canon law : comparative approach to marital ties and new perspectives - (:unkn) unknown (My University, 2019)
The study of family law in general, the social and the foundation of all human activity, allows to have an overall vision of family life and to discover the basis of interpersonal relationships. In this context, considering the matrimonial problems which often arise within the different civilizations, an in-depth study on marriage and its possible dissolution in the African context, in particular with regard to the different rights that govern, is of major importance. The existence of a matrimonial relationship between the man and the woman who unite in marriage is recognized in the akyã custom, in Ivorian civil law and in canon law. The problem of the indissolubility of this matrimonial relationship in the Catholic Church arises both in Africa and in Europe. Indeed, if according to customary rules and civil laws, divorce and remarriage are possible, the doctrinal and legal provisions of the Catholic Church do not allow them when the celebrated unions are blameless. The thesis work intends to make a modest contribution to the resolution of these problems. Thus, will it be for us in the pastoral field to present a convincing argument for the official declaration of the sacramentality of African customary marriage and for the insertion of certain African matrimonial provisions in the Canon law of the Catholic Church.
Keywords: African Research